Workshop Penerapan Penelitian Tindakan Kelas (Ptk) Berbasis Lesson Study Di SD Negeri 10 Rappang - Hermansyah, Sam; M, Usman; R Kasau, M. Nurzin (Universitas Sumatera Barat, 2023)
The objectives of this activity are 1) to provide a correct understanding regarding the implementation of Lesson Study-based Classroom Action Research, 2) to help teachers identify learning problems that can be corrected by implementing Lesson Study-based Classroom Action Research. This service activity is delivered using lecture, question and answer, discussion and performance methods during lesson study-based PTK workshops, resulting in problem identification that focuses on the background of the problem and a research title that is appropriate to the problem identified. Several things that can be followed up from this service activity are that lesson study based PTK activities should be carried out continuously and continuously with intensive assistance from the lecturer (service team) so that the activity is not finished during the workshop; as a form of follow-up to the workshop activities themselves; routine measurements are needed to determine the impact of LS-based PTK activities on solving various problems found during the workshop; The implementation of lesson study can be successful if the teacher carries out and practices as well as implements in his class all the lesson study programs that have been followed in MGMP and workshops; The role of the principal himself is to give permission for teachers to take part in MGMP activities, to control the presence of teachers in MGMP, to provide input during reflection, and especially the role of the principal to provide funds for the implementation of the Lesson Study program.